2019
DOI: 10.1121/1.5096178
|View full text |Cite
|
Sign up to set email alerts
|

A round robin on room acoustical simulation and auralization

Abstract: A round robin was conducted to evaluate the state of the art of room acoustic modeling software both in the physical and perceptual realms. The test was based on six acoustic scenes highlighting specific acoustic phenomena and for three complex, “real-world” spatial environments. The results demonstrate that most present simulation algorithms generate obvious model errors once the assumptions of geometrical acoustics are no longer met. As a consequence, they are neither able to provide a reliable pattern of ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 27 publications
2
65
1
7
Order By: Relevance
“…Previous studies regarding the realism of binaural (i.e., rendered via headphones) auralizations have mainly focused on comparing auralizations based on simulated sound fields to those based on measured sound fields, see e.g. [6][7][8][9][10]. The latent (and sometimes explicitly formulated) assumption underlying the cited studies is that measurements represent the "reality" and that simulations could also represent the reality if they were indistinguishable from measurements in the direct comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies regarding the realism of binaural (i.e., rendered via headphones) auralizations have mainly focused on comparing auralizations based on simulated sound fields to those based on measured sound fields, see e.g. [6][7][8][9][10]. The latent (and sometimes explicitly formulated) assumption underlying the cited studies is that measurements represent the "reality" and that simulations could also represent the reality if they were indistinguishable from measurements in the direct comparison.…”
Section: Introductionmentioning
confidence: 99%
“…This is important since an evaluation of current acoustic modeling algorithms showed that they can generate plausible but not entirely authentic simulations, i.e. human observers could distinguish simulations from recordings (Brinkmann et al, 2019). Nevertheless, our study shows that the cognitive effects of acoustic inventions can be successfully obtained in VR, as highlighted by earlier work that successfully measured the cognitive effects of simulated acoustic insulation (Muhammad et al, 2019).…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, absence of diffraction does not prohibit plausible rendering in room acoustics. Rather, it is desired to boost accuracy [BAA*19]. With these practical considerations, ray‐tracing methods that start with a diffraction‐less geometric approximation are standard in room acoustics [Vor07].…”
Section: Introductionmentioning
confidence: 99%